PENGARUH LEVERAGE TERHADAP PENGUNGKAPAN ISLAMIC SOCIAL REPORTING DENGAN AKUNTABILITAS DAN TRANSPARANSI SEBAGAI VARIABEL MODERATING PADA PERBANKAN SYARIAH DI INDONESIA PERIODE 2012-2016 - Eksandy, Arry (Universitas Muhammadiyah Tangerang, 2018)
This research aims to determine the effect of LeverageFinancing on the Disclosure of Islamic Social Reporting (ISR) with moderated by Accountability and the Transparency. The population in this research is all sharia banking in the form of Sharia Commercial Bank in Indonesia during the period 2012-2016. The total samples tested were 9 Sharia Commercial Bank selected by purposive sampling technique. This research analyzes ISR Index through bank annual report by using content analysis method. Data analysis technique use panel data regression with Eviews 9.0 program.The results describe Accountability and Transparency able to moderate the relationship of Leverageto the Disclosure of Islamic Social reporting. Leverage have no effect on the disclosure of Islamic Social reporting, but after moderated by Accountability and the Transparency of Leverage has a negative effect on Disclosure of Islamic Social Reporting.Keywords: Disclosure of Islamic Social Reporting (ISR), Debt to Assets Ratio, Accountability and Transparency